On the classes of analytic functions involving A1-Oboudi operator - Mahzoon, Hesam; Latha, S.
In this note, we define the new subclasses N m,n(b, α, β, λ) and̃Nm,b, α, β, λ) of analytic functions using the Al -oboudi operator. For functions belonging to these classes we determine coefficient inequalities, extremepoints and integral means inequalities.
Keywords: Analytic functions; Al-Oboudi operator; Coefficient inequalities; Extreme points and integral means